Systematic review of studies investigating the association between dietary habits and cutaneous malignant melanoma. Issue 8 (August 2015) - de Waure, C.; Quaranta, G.; Gualano, M.R.; Cadeddu, C.; Jovic-Vranes, A.; Djikanovic, B.; La Torre, G.; Ricciardi, W.
Abstract Objective Several papers have dealt with diet as a risk factor for cutaneous malignant melanoma (CMM). This study aimed to synthesize available data on the topic. Study design A systematic review of observational studies assessing the association between dietary habits and CMM was performed. Methods Electronic databases were used to identify eligible articles. Quality was assessed through the Newcastle–Ottawa scale. Case–control and cohort studies evaluating the intake of food/nutrients through the assessment of dietary habits and the occurrence of CMM were considered eligible. Data comparing the highest and lowest levels of consumption were collected from single studies and described qualitatively as data combination was not possible. Results were reported as percentages on the basis of relative risks and odds ratios. Results Eighteen studies reported in 21 articles were selected. Cohort studies showed better quality than case–control studies. Most articles did not detect any significant association between food/nutrient intake and CMM, except for limited evidence of a protective role associated with fish, vegetables and fruit. Risk reduction was shown to be 35–37%, 40–57% and 34–46%, respectively, in studies reporting significant results. Similarly, few articles showed protective roles of beta-carotene and vitamins A, C, D and E, with risk reduction of 64%, 37–43%, 41%, 15–39% and 50–66%, respectively. Conclusion A trend towards reduced risk of CMM associated with higher intake of fish, vegetables and fruit, as well as beta-carotene and vitamins A, C, D and E, has been shown but further research is needed to provide decisive data.